2011
DOI: 10.1055/s-0031-1279986
|View full text |Cite
|
Sign up to set email alerts
|

Die Mammareduktionsplastik in Deutschland – Ergebnisse einer multizentrischen Erhebung

Abstract: Einleitung: Die Kostenübernahme für eine Reduktionsplastik als Therapie eines Überlastungs-syndroms bei Mammahypertrophie wird von den Kostenträgern zunehmend restriktiv gehandhabt. Die Effektivität des Eingriffs in Deutschland soll dargestellt werden. Material und Methode: Mit 461 ausgewerteten Patienten aus 18 AWOgyn-Kliniken (Arbeitsgemeinschaft für ästhetische, plastische und rekonstruktive Operationen in der Gynäkologie), die mit einem validierten, sog. MRP-Fragebogen untersucht wurden, wird die bislang u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
14

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 7 publications
1
3
0
14
Order By: Relevance
“…Regardless of the costs for each category, the usefulness of each form of treatment has to be assessed. Several studies have evaluated the effect of weight reduction, for example, and found that it did not have any positive effects on the symptoms of macromastia [ 2 , 11 , 20 ]. The resources, including costs, that are devoted to weight reduction are therefore of very limited effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the costs for each category, the usefulness of each form of treatment has to be assessed. Several studies have evaluated the effect of weight reduction, for example, and found that it did not have any positive effects on the symptoms of macromastia [ 2 , 11 , 20 ]. The resources, including costs, that are devoted to weight reduction are therefore of very limited effect.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, pain relief is achieved by medication alone. Insurance companies sometimes advise the patient to undergo rehabilitation measures [ 11 , 14 , 19 , 20 , 28 ]. However, none of these conservative treatments has shown sufficient and long-lasting effects, as they do not represent causal therapies [ 11 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patientinnen mit einer Makromastie leiden deshalb besonders unter Nackenschmerzen, Schulterschmerzen und Rückenschmerzen, sowohl in der Brustals auch in der Lendenwirbelsäule [12,20,22,39,40,48,76,102,109,110,118,125,132,134]. Daraus folgt eine unphysiologische Körperhaltung [39,40,76,86,110,132] und in den o.g.…”
Section: Physische Beschwerdebilderunclassified
“…Daraus folgt eine unphysiologische Körperhaltung [39,40,76,86,110,132] und in den o.g. anatomischen Bereichen kommt es durch die Fehlbelastung zu schmerzhaften Myogelosen (Muskelverhärtungen) [86,134].…”
Section: Physische Beschwerdebilderunclassified
See 1 more Smart Citation